Urban Development Planning: The Need for a New Paradigm - Kumar, Vikas; Yadav, Chhavi (Journal of Commerce and Trade, 2014)
Planning solutions are viewed as a strategy for building new cities and as a means for upgrading existing cities. Little clarity, however, exists about the constituents of possible new paradigms of urban planning. This paper has two objectives. The first is to draw some conclusions from past experience on building new cities and upgrading existing ones. The DP and its process should not be used to reify boundaries between legality and illegality as interpretations of what is legal and illegal are subject to change and are unduly influenced by certain groups. Rather, it should focus on enhancing the functionality of the city. An important strategy for operationalizing this is to promote the viability of the informal sector. This will enhance the quality of life of many people as well as the growth of the formal economy to which the informal sector is closely linked.